Nutritional anti-inflammatories in the treatment and prevention of type 2 diabetes mellitus and the metabolic syndrome. (May 2017) - Merone, Lea; McDermott, Robyn
Highlights: Obesity is a key factor for developing Metabolic Syndrome and Type 2 Diabetes. This review provides an overview of nutritionally based anti-inflammatories. Polyphenols are anti-inflammatory in Metabolic Syndrome and Type 2 Diabetes. Recent evidence regarding fish oils is modest. Vitamin supplementation also has anti-inflammatory effects. Abstract: Aims: Obesity-fuelled metabolic syndrome and diabetes is now a global epidemic. There is increasing evidence that these and other chronic conditions have common inflammatory antecedents. There is an interest in nutritionally based anti-inflammatory treatments for type 2 diabetes and metabolic syndrome. The aim of this review is to examine the evidence from a 5-year period; 2011–2016, for nutritionally based anti-inflammatory treatments for the Metabolic Syndrome and Type 2 Diabetes Mellitus. Methods: A literature search produced a total number of 1377 records, of which 26 papers were evaluated. Results: Literature was analysed and tabulated according to date, outcome measures and results. Conclusion: The evidence is strong for use of polyphenolic compounds, fish oils and vitamins in reducing inflammation biomarkers, however the impact on metabolic control is less evident.